Experimental study of fracture energy for foamed concrete - Nasrullah, Alsad (2021)
Foamed concrete has recently gained attention as an alternative material to normal concrete in structural engineering. As a structural component, foamed concrete has many advantages given its characteristics such as high strength with low density, good serviceability, and lightweight. Therefore, many studies have been investigated for their strength and mechanical properties. However, literature has shown that there is a lack of research on fracture energy of foamed concrete, which is the main parameter that governs damage and cracks mechanisms of any structural components. Therefore, the present study aims to experimentally investigate the fracture energy of foamed concrete using beam specimens with U-notch and V-notch through a three-point bending test. Fifty-two (52) foamed concrete beam specimens with 100 mm x 100 mm x 800 mm in length with a density of 1600 kg/m³ were cast. The foamed concrete compressive strength of approximately 9 to 10 MPa was achieved at 28 days. Of the fifty-two numbers of beam specimens, two beams were cast as control specimens (with no notches) whilst the fortyeight number of beam specimens was provided with various variables including different